Transitions in Care: A Workshop to Help Residents and Fellows Provide Safe, Effective Handoffs for Acute Psychiatric Patients - Amber Frank (Association of American Medical Colleges, 2020)
Introduction Focused training in care transitions is an ACGME-required component of resident education. However, there are limited published curricular resources specific to trainees in psychiatry to help develop this crucial skill. Methods We developed a 90-minute interactive workshop on care transitions in psychiatry for general adult psychiatry residents (PGY 2-PGY 4), child and adolescent fellows, and consult-liaison fellows. Trainees collaborated in interdisciplinary teams to explore a vignette in which a patient moved through four different venues of care (outpatient, emergency department, inpatient medical, and inpatient psychiatric). Guiding questions prompted discussions of critical issues related to logistics and clinical communication for each transition between care environments. Results In a postworkshop anonymous survey, 100% of trainee participants (n = 30) felt the workshop was successful in creating the opportunity to develop relationships with, and learn from, colleagues at other levels of psychiatry training. Ninety percent responded affirmatively that they were able to identify key elements of an effective handoff for an acute psychiatric patient. Eighty-three percent identified being able to describe logistical steps for transferring the care of patients between mental health services at their institution. Discussion Trainee participants found the workshop beneficial for understanding the steps needed to transfer patients between levels of care safely, discussing and debating gray areas with peers and faculty, and developing interdisciplinary relationships within psychiatry. Faculty participants described an interest in using the workshop as a faculty development exercise. This workshop fills a critical gap in available curricula on transitions in care in psychiatry.